A case report of an incidental Brenner tumor found after resection of a large ovarian mucinous neoplasm. (2018) - Dougherty, Danielle; Onyemkpa, Chibueze; Engel, Michael; Oyasiji, Tolutope
Highlights: A case report of a Brenner tumor incidentally associated with a mucinous ovarian tumor is presented. The frozen section was diagnosed as benign and the Brenner's tumor was noted. Final pathological report revealed borderline classification of tumor. It is unknown whether an associated Brenner's tumor increases risk of malignancy. A better understanding of this relationship could help guide intraoperative decision making. Abstract: Introduction: Brenner Tumors are rare adenofibromas that are most commonly benign and discovered in post-menopausal women. Presentation of case: This is a case report of a 57-year-old female with three months of progressively worsening abdominal pain due to a large abdominal mass discovered on CT scan. Surgical removal of the mass revealed a giant mucinous tumor of the ovary with an associated Brenner tumor that was discovered incidentally. Discussion: Although the Brenner tumor was accurately identified in the intraoperative frozen section evaluation, the mucinous tumor was underdiagnosed by frozen section as benign when permanent section revealed borderline mucinous cystadenoma. This finding did not change the treatment course for this particular patient as she had expressed personal preference for total abdominal hysterectomy. However, underdiagnosis of frozen sections of ovarian tumors is not rare. It is unclear whether an associated Brenner tumor increases malignancy potential. Conclusion: Further investigation is required to determine whether associated Brenner tumors found during frozen section are more highly associated with malignancy and could therefore change intraoperative and overall decision making.